Increasing maternal obesity is associated with alterations in both maternal and neonatal thyroid hormone levels. (16th December 2015) - Kahr, Maike K.; Antony, Kathleen M.; DelBeccaro, Melanie; Hu, Min; Aagaard, Kjersti M.; Suter, Melissa A.
Summary: Objective: Obesity is associated with alterations in thyroid hormone (TH) levels in obese, pregnant individuals. The maintenance of TH levels throughout gestation is important for proper foetal development. The aim of this study was to measure levels of fT3, fT4 and TSH in maternal and matched cord blood serum from normal weight, overweight and obese gravidae to determine alterations in maternal and neonatal TH levels by virtue of maternal obesity. Design, Setting, Subjects, Outcome Measures: ELISA was utilized to measure fT3, fT4 and TSH levels from banked, matched maternal and neonatal (cord blood) serum ( N = 205 matched pairs). Data were stratified according to prepregnancy or first trimester BMI. Results: Both maternal and neonatal fT3 levels consistently increased with increasing maternal obesity, and maternal and neonatal fT3 were significantly correlated ( r = 0·422, P < 0·001). Maternal and neonatal fT3 were also significantly associated with birthweight (β = 0·155, P = 0·027 and β = 0·171, P = 0·018, respectively). Both the maternal and neonatal fT3 to fT4 ratio significantly increased with increasing maternal obesity. We further found that excess gestational weight gain was associated with a decrease in maternal fT4 compared with gravidae who had insufficient gestational weight gain (0·86 ± 0·17 vs 0·95 ± 0·22, P < 0·01). Conclusion: Maternal obesity is not only associated with maternal alterations in TH, but with accompanying neonatal changes. Because both maternal obesity and alterations in TH levels are associated with childhood obesity, based on these findings and our prior analyses in a nonhuman primate model, we propose that changes in fT3 levels in the offspring of obese mothers may be a potential molecular mediator of foetal overgrowth and childhood obesity.